Blast Fishing Activity and Coping Strategies in Indonesia (South Nias and Pohuwato Regency) - Saragih, Rina Fariani; Trencher, Gregory (Jurnal Ilmiah Administrasi Publik, 2020)
Indonesia is one such country that has not yet been successful with strategies of the government to cope with the blast fishing problem.Â In the existing literature, many scholars tend to study the impact of blast fishing activity from a social and ecological perspective, and few works focus on examining the governance arrangements in place to tackle blast fishing, the effectiveness of these, and how they might be improved. This research uses the case of South Nias and Pohuwato Regency in Indonesia to understand and analyses the factors affecting the outcomes of governance measures to cope with blast fishing. Findings revealed that the blast fishing situation is less improved in South Nias but significantly reduced in Pohuwato. The existing strategies in South Nias have not succeeded in eradicating the blast fishing activity of because of the lack budget and resources for implementing preventative actions. In contrast, in Pohuwato, the involvement of resource users, the co-ordination of government institutions, sharing of resources between the authorities and the community appear to be the main factors that have contributed to more effective governance measures and a decline in blast fishing activity.